La expedición a Loma Rica revisitada. Los inicios arqueológicos: entre los intereses provinciales y el avance de la centralización estatal (Tucumán, 1877) - Sandra Tolosa (Cahiers des Amériques Latines)
In this article I propose a re-examination of the sources related to the Archaeological Expedition of Inocencio Liberani and Rafael Hernández to Loma Rica, Catamarca, Argentina, which took place in 1877. The aim is to focus both on the role played by the local agency in its management and implementation, which reflected the interests of the provincial elite, and also on the way it was affected by the framework of the centralization process that was being applied to science and public instruction by the newly-established nation-state.